Prehospital cooling to improve successful targeted temperature management after cardiac arrest: A randomized controlled trial. (December 2017) - Scales, D.C.; Cheskes, S.; Verbeek, P.R.; Pinto, R.; Austin, D.; Brooks, S.C.; Dainty, K.N.; Goncharenko, K.; Mamdani, M.; Thorpe, K.E.; Morrison, L.J.; ,
Abstract: Rationale: Targeted temperature management (TTM) improves survival with good neurological outcome after out-of-hospital cardiac arrest (OHCA), but is delivered inconsistently and often with delay. Objective: To determine if prehospital cooling by paramedics leads to higher rates of 'successful TTM', defined as achieving a target temperature of 32–34 °C within 6 h of hospital arrival. Methods: Pragmatic RCT comparing prehospital cooling (surface ice packs, cold saline infusion, wristband reminders) initiated 5 min after return of spontaneous circulation (ROSC) versus usual resuscitation and transport. The primary outcome was rate of 'successful TTM'; secondary outcomes were rates of applying TTM in hospital, survival with good neurological outcome, pulmonary edema in emergency department, and re-arrest during transport. Results: 585 patients were randomized to receive prehospital cooling (n = 279) or control (n = 306). Prehospital cooling did not increase rates of 'successful TTM' (30% vs 25%; RR, 1.17; 95% confidence interval [CI] 0.91–1.52; p = 0.22), but increased rates of applying TTM in hospital (68% vs 56%; RR, 1.21; 95%CI 1.07–1.37; p = 0.003). Survival with good neurological outcome (29% vs 26%; RR, 1.13, 95%CI 0.87–1.47; p = 0.37) was similar. Prehospital cooling was not associated with re-arrest during transport (7.5% vs 8.2%; RR, 0.94; 95%CI 0.54–1.63; p = 0.83) but was associated with decreased incidence of pulmonary edema in emergency department (12% vs 18%; RR, 0.66; 95%CI 0.44–0.99; p = 0.04). Conclusions: Prehospital cooling initiated 5 min after ROSC did not increase rates of achieving a target temperature of 32–34 °C within 6 h of hospital arrival but was safe and increased application of TTM in hospital.